2020
DOI: 10.1051/ocl/2020023
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on sunflower broomrape research in China

Abstract: Broomrape (Orobanche cumana Wallr.) is a holoparasitic plant which parasites sunflower roots. The infected sunflower plants are smaller, have a reduced kernel/husk ratio and yield decreases dramatically. It has become a severe problem for sunflower production all over the world. In recent years, due to importation of sunflower hybrid seeds, frequent local seed transportation and insufficient plant quarantine, broomrape widely occurs in sunflower production areas of China. This review addresses recent research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…aegyptiaca in China. Orobanche cumana was reported mainly on sunflower in Inner Mongolia, Xinjiang, Heilongjiang, Jilin, Shanxi, Shaanxi, Hebei, Gansu, and Ningxia provinces (Shi & Zhao, 2020 ; Wu et al, 2020 ). The model's simulation results highlighted that the suitable areas of O .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…aegyptiaca in China. Orobanche cumana was reported mainly on sunflower in Inner Mongolia, Xinjiang, Heilongjiang, Jilin, Shanxi, Shaanxi, Hebei, Gansu, and Ningxia provinces (Shi & Zhao, 2020 ; Wu et al, 2020 ). The model's simulation results highlighted that the suitable areas of O .…”
Section: Discussionmentioning
confidence: 99%
“…The predictive models constructed with MaxEnt were highly consistent with the known distribution of O. cumuan and P. aegyptiaca in China. Orobanche cumana was reported mainly on sunflower in Inner Mongolia, Xinjiang, Heilongjiang, Jilin, Shanxi, Shaanxi, Hebei, Gansu, and Ningxia provinces (Shi & Zhao, 2020;Wu et al, 2020) temperatures required for its conditioning and germination, which was found to be around 25-30°C: both lower and higher temperatures resulted in poor germination (Shi et al, 2018). Meanwhile, this also may be attributed to transitory or constantly high atmospheric temperatures causing a series of heat injuries, physiological disorders, and morphological and biochemical changes in plants (Lipiec et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sunflower has been widely cultivated in northeast China. After the seeds are used for oil extraction, sunflower receptacles have largely been discarded [ 4 , 5 , 6 ], which not only wastes resources, but also pollutes the environment. Sunflower receptacles contains many active compounds, including flavonoids [ 7 , 8 ], alkaloids [ 9 , 10 ], and chlorogenic acid [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%